Trends in incidence of pneumothorax in England before, during and after the COVID-19 pandemic (2017–2023): a population-based observational studyResearch in context - Xiaomin Zhong; Raph Goldacre; Eva J.A. Morris; Rob J. Hallifax (The Lancet Regional Health. Europe, 2024)
Summary: Background: COVID-19 is a risk factor for pneumothorax. The pandemic may have influenced healthcare-seeking behaviour for pneumothorax. This study aimed to investigate recent trends in the incidence of pneumothorax in England. Methods: A population-based epidemiological study was conducted using an English national dataset of hospital admissions (Hospital Episode Statistics) from 2017 to 2023. Record-linkage was used to identify multiple admissions per person and co-morbidity. Pneumothoraces co-occurring with COVID-19 were identified by concurrent COVID-19 diagnostic coding. The pre-pandemic (January 2017–February 2020), pandemic (March-2020–February-2021) and post-pandemic periods (March 2021–March 2023) were compared. Findings: From 2017 to 2023, there were 72,275 hospital admissions for spontaneous pneumothorax among 59,130 patients. Admissions showed marked variability, peaking in January 2021 when the rate of admissions was about two-thirds higher than that of the pre-pandemic level (Incidence rate ratio [IRR] 1.65, 95% CI: 1.48–1.84). However, when excluding patients with a concurrent COVID-19 diagnosis, the overall trend shifted to a reduction during the pandemic period. Post-pandemic rates were not significantly different from pre-pandemic levels (IRR = 0.96, 95% CI: 0.89–1.04). The incidence of spontaneous pneumothorax was significantly higher in males (rate ratio compared to females: 2.29, 95% CI: 2.19–2.39). However, the trends were consistent in both males and females. Interpretation: This study highlights a significant peak in COVID-19 related cases but a corresponding trough in non-COVID-related cases (end 2020, early 2021). Despite a previous report of increasing incidence of (non-COVID-related) hospitalised spontaneous pneumothorax over the long-term between 1968 and 2016, we did not observe any continued increase throughout this study period, prompting further investigation into the impact of recent guidelines. Funding: Authors are supported by the NIHR Oxford BRC, Li Ka Shing and Robertson Foundations, MRC, and HDR UK.